El subtítulo amateur al francés de Ocho apellidos vascos: la traducción de los estereoti- pos, las identidades culturales y el multilingüismo - García, Francisca (Anales de Filología Francesa, 2018)
This article aims to carry out a descriptive analysis of the translation strategies and techniques used in the French amateur subtitles of the film Ocho apellidos vascos (Spanish Affair, 2014), strongly characterized by multilingualism and multiculturalism. It is a corpus where concepts such as language, identity and prejudices acquire a special relevance, given that the comedic plot of the film is based in a combination of all of them. Thus, the interest in studying how all these references have been translated into a language that ignores many of them.